Primary Care Clinical Practice Guidelines and Referral Pathways for Oral and Dental Diseases in Pakistan - Syeda Sehrish Haider; Russell Seth Martins; Rohaid Ali; Nashia Ali Rizvi; Mohsin Ali Mustafa; Salima Saleem Aamdani; Alina Abdul Rehman; Alina Pervez; Sarah Nadeem; Humayun Kaleem Siddiqui; Ali Sadiq; Syed Murtaza Raza Kazmi; et al. (MDPI AG, 2024)
Background: The provision of dental care in Pakistan is limited, with less than 5% of the population having access to qualified dental practitioners. The lack of contextually relevant local dental guidelines further adds to the problem. We developed clinical practice guidelines (CPGs) and referral pathways to improve primary care for common oral diseases. Methods: Using the GRADE-ADOLOPMENT approach, recommendations from source guidelines (developed in Europe and the United States) were adopted (retained as is or with minor changes), adapted (modified according to the local context), or excluded (omitted due to lack of local relevance). The guidelines included diseases such as periodontitis, dental pain, intraoral swelling, and oral cavity malignancies. The end result was a set of locally relevant CPGs, which were then used to formulate referral pathways, with the incorporated suggestions being based on a thorough evidence review process. Results: We included four recommendations, three of which were adopted with minor modifications to the referral pathway. These changes focused on assessing potentially malignant oral conditions and counseling for risk factors. No content changes were needed for the CPGs of the other two disorders. We developed referral pathways for three specific oral conditions, detailing primary care physicians' roles in diagnosis, initial treatment, and timely referral. Conclusion: Contextually relevant dental CPGs and referral pathways can improve patient outcomes in Pakistan. Our study produced four additional recommendations focused on risk factor counselling and mitigation, which could potentially reduce the burden of oral malignancies in our local population.